Management ofcash flows ofinvestment activity ofenterprises - RENDOVYCH, Petro (Scientific journal «World of Finance», 2019)
Introduction. In joint-stock companies there is a problem of shortage of money not only for carrying out of investment activity, but also for maintenance of sufficient level of the operational activity. One of the main instruments of a market economy that contributes to the formation of a cash flow system is the stock market.The purpose ofthe article is to study some aspects ofcash flow management in the system of financial management, to characterize cash flows of joint stock companies, which determine the potential of forming their internal source of financing for their development and provide the formation of additional investment resources for the implementation of financial investments in the securities market.Results. One of the important tasks of the Ukrainian economy development is the development of mechanisms for the formation of investment-attractive and innovative-oriented joint-stock companies. The development of market relations requires an increase in the effectiveness of their activities. The assessment of the effective activity of the entity was determined by analyzing the profit of the enterprise, and subsequently, economists supplemented its coefficients of liquidity, solvency, financial stability. The analysis and identification ofthe reserves for increasing profits is also carried out by analysts of the stock market in orderto furtherstimulate the investor.Conclusion. We believe that the analysis of cash flows by their dynamics and structure allows us to identify the negative factors of the organization of financial and economic activity of the entity, immediately reflects the size, quality and direction of change in the financial state of the joint-stock company, and also contributes to the development of concrete measures for its improvement. Since inbound and outbound cash flows of investments are the main factors in creating the value ofenterprises, which ultimately reflects the management of the result of investment activity in terms of Modern Value Approach, therefore, in our view, the process of reproduction of capital and the formation of investment flows can be expressed through the movement of value in the field Investment activity. In the process of studying investment flows of enterprises, it was found that the level of investment attractiveness of enterprises depends on the efficiency of the movement oftheirinvestment cash flows.